Providing Services During Times of Change: Can Employees Maintain Their Levels of Empowerment, Work Engagement and Service Quality Through a Job Crafting Intervention? - Hulshof, Inge L.; Demerouti, Evangelia; Le Blanc, Pascale M. (Frontiers in Psychology, 2020)
By means of a quasi-experimental study, the effects of a tailor-made job crafting intervention for employees of a Dutch unemployment agency were evaluated. The intervention was designed to prevent a decrease in employee empowerment, work engagement and employee performance (i.e., the provision of services) due to organizational changes. Seventy-four employees received a 1-day training in which they set 4 job crafting goals for the subsequent weeks. After 6 weeks a reflection session was organized. Repeated measures ANOVA’s showed that the intervention prevented a decrease in employees’ feelings of empowerment. Furthermore, pre-post comparison tests showed that the control group (N = 89) experienced a significant decrease in work engagement, whereas the intervention group did not. Results showed no effect on customer-rated employee service quality. However, one year after the intervention, customer ratings of employee service quality were significantly higher for the intervention group compared to the control group. Although further research is needed, our results demonstrate that a job crafting intervention may be a promising tool to combat a decline in employee empowerment and work engagement during times of organizational change.